2001
DOI: 10.1128/jvi.75.2.903-909.2001
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Integration of Transduced Recombinant Baculovirus DNA in Mammalian Cells

Abstract: Our group and others have recently demonstrated the ability of recombinant baculoviruses to transduce mammalian cells at high frequency. To further characterize the use of baculovirus as a mammalian gene delivery system, we examined the status of transduced DNA stably maintained in Chinese hamster ovary (CHO) cells. Four independent clones carrying two introduced markers, the genes for neomycin resistance (Neo) and green fluorescent protein (GFP), were selected. PCR analysis, Southern blotting, and DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 32 publications
0
55
0
1
Order By: Relevance
“…Two pairs of primers specific to two fragments on the baculoviral genome (BM3 and BM4) were designed as described. 48 PCRs were performed using 100 ng of genomic DNA and the PCR products were subjected to 0.8% agarose gel electrophoresis. 48 The FISH experiments were performed as described with minor modifications.…”
Section: Pcr and Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pairs of primers specific to two fragments on the baculoviral genome (BM3 and BM4) were designed as described. 48 PCRs were performed using 100 ng of genomic DNA and the PCR products were subjected to 0.8% agarose gel electrophoresis. 48 The FISH experiments were performed as described with minor modifications.…”
Section: Pcr and Fishmentioning
confidence: 99%
“…48 PCRs were performed using 100 ng of genomic DNA and the PCR products were subjected to 0.8% agarose gel electrophoresis. 48 The FISH experiments were performed as described with minor modifications. 20 The mitotic cells were prepared at 24 d.p.t.…”
Section: Pcr and Fishmentioning
confidence: 99%
“…In some cases, however, instability appears to be restricted to the time of integration. Many studies carried out in cultured cells 41,47,48,53 and transgenic mouse lines 43 have shown that while vectors can be physically rearranged initially, expansion of cell or mouse lines reveals no further rearrangements. This leads to the conclusion that the deletions and rearrangements observed are sometimes early events in the integration process.…”
Section: Recipient Genomic Loci Are Often Unstable After Illegitimatementioning
confidence: 99%
“…It appears that exogenous DNA generally integrates at one, or very few, site(s) in the recipient genome, but often in multiple copies showing the presence of 1-6 bp of microhomology or slight degrada- Illegitimate DNA integration H Würtele et al tion or addition of nucleotides at transgene-transgene junctions. [41][42][43][44][45][46][47] The NHEJ activities capable of circularizing and concatemerizing extrachromosomal DNA have been suggested to account for randomly oriented transgene arrays, while the frequent appearance of tandem arrays comprised of direct repeats is best explained by homologous recombination between circular and linear molecules before or during the integration process. 41,42 The organization and quantity of integrated DNA appear to vary according to cell type.…”
Section: Introductionmentioning
confidence: 99%
“…8 Baculoviral DNA degrades in the cells over time 13,20 and there is no evidence of baculoviral DNA integration into host chromosomes in the absence of selective pressure. 21 These attributes minimize the potential side effects and ease the safety concerns. Furthermore, the large baculovirus genome confers a huge cloning capacity of up to 38 kb 22 and baculovirus can be propagated to high titers easily by infecting its natural host insect cells.…”
Section: Discussionmentioning
confidence: 99%